Race-Specific Trends in Prostate Cancer Screening and Presentation before and after the 2012 United States Preventive Services Task Force Statement. Issue 1 (2nd January 2022) - Horton, Brandon; Alexeeff, Stacey; Prausnitz, Stephanie; Avins, Andrew L.; Presti, Joseph
Abstract: Introduction: Our goal was to assess temporal changes in the race-specific rates of prostate specific antigen (PSA) screening, prostate biopsy, overall prostate cancer detection and metastatic cancer at presentation among screen-eligible men in Kaiser Permanente Northern California before and after the 2012 United States Preventive Services Task Force Prostate Cancer Screening Statement. Methods: This was a retrospective study spanning the years 2006 to 2017 in screen-eligible Kaiser Permanente Northern California members (Black men ages 45–69, all other men ages 50–69) with no history of prostate cancer. We compared the race-specific biennial rates of PSA testing, prostate biopsy, overall prostate cancer incidence and metastatic cancer at presentation. Results: A total of 422, 664 to 567, 660 men per biennial period were evaluated (72% White, 8% Black, 20% Asian). Following the 2012 United States Preventive Services Task Force statement, all races experienced similar declines in screening (22%–25%), biopsy (47%–57%) and overall cancer detection (34%–48%) rates. We found an increase in metastatic rates (39%–105%). Conclusions: Following the 2012 United States Preventive Services Task Force Statement, in men under the age of 70, PSA screening, biopsy and overall prostate cancer detection rates significantly decreased in a similar fashion across all races, while rates of metastatic disease significantly increased in all races.